Analisis Penyusunan Laporan Keuangan Pada Usaha Mikro Dedik Lukisan - Putri, Ni Kadek Dewi Harnika; Wati, Ni Wayan Alit Erlina (UNHI Press, 2025)
This research investigates how Dedik Lukisan, a micro-scale enterprise, prepares its financial reports and evaluates their alignment with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM). Utilizing a combination of observations, interviews, and document analysis, the study explores the company’s accounting and reporting practices. The results indicate that Dedik Lukisan’s financial reporting remains basic and has yet to fully implement the guidelines set by SAK-EMKM, as the records only include cash inflows and outflows without a complete structure such as a statement of financial position or income statement. The main factors influencing this are the limited knowledge of the owner and the absence of a computerized accounting system. This study concludes that the implementation of SAK-EMKM is crucial to improve the quality of financial statements for micro businesses, which in turn can support better business management, decision-making, and access to external funding sources.